Navy Shore Establishment Realignment (SER)--A Very, Very, Very Expensive "Savings." Can We Afford It?
An information sheet examining the cost of a Navy Shore Establishment Realignment which would move functions performed by the Navy Civil Engineering Lab to other locations. Includes purported savings.